2018
DOI: 10.1371/journal.pone.0204475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a VapA virulence factor functional homolog in Rhodococcus equi isolates housing the pVAPB plasmid

Abstract: Rhodococcus equi is a facultative intracellular bacterium of macrophages and is an important pathogen of animals and immunocompromised people wherein disease results in abcessation of the lungs and other sites. Prior work has shown that the presence of the major virulence determinant, VapA, encoded on the pVAPA-type plasmid, disrupts normal phagosome development and is essential for bacterial replication within macrophages. pVAPA- type plasmids are typical of R. equi strains derived from foals while strains fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…mice, apparently also humans). This critical vap determinant is probably the common ancestor of vapA of the equine pVAPA type and its allelic variants vapN of the ruminant pVAPN type (Valero‐Rello et al , ) and vapK1/2 (and putative duplicate thereof, vapB ) of the porcine pVAPB type (Valero‐Rello et al , ; Willingham‐Lane et al , ) (Fig. A and B).…”
Section: Evolution Of R Equi Virulencementioning
confidence: 99%
“…mice, apparently also humans). This critical vap determinant is probably the common ancestor of vapA of the equine pVAPA type and its allelic variants vapN of the ruminant pVAPN type (Valero‐Rello et al , ) and vapK1/2 (and putative duplicate thereof, vapB ) of the porcine pVAPB type (Valero‐Rello et al , ; Willingham‐Lane et al , ) (Fig. A and B).…”
Section: Evolution Of R Equi Virulencementioning
confidence: 99%
“…The pathogenicity of “ R. equi” is mediated by Virulence Associated Proteins (VAPs) encoded on the acquired pathogenicity islands (PAIs) of host-adapted conjugative virulence plasmids [ 89 ]. “ R. equi ” isolates from equine, porcine, and bovine samples carry different types of plasmids called pVAPA, pVAPB, and pVAPN, respectively [ 90 ].…”
Section: Ubiquity Of Rhodococcus and Existence Of Pathogenic Speciesmentioning
confidence: 99%
“…The pVAPB plasmid consists of vapB, -J, -K1, -K2, -L , and -M , whereas pVAPN carries vapN, -O, -P , and -Q genes. VapK1, vapK2, vapB , and vapN are functionally equivalent to vapA [ 90 , 94 , 95 ].…”
Section: Ubiquity Of Rhodococcus and Existence Of Pathogenic Speciesmentioning
confidence: 99%
“…Each bacterial isolate contains either only one plasmid type or none ( 15 ). A total of 21 vap genes and pseudogenes are known; four of these ( vapA , vapK1 , vapK2 , and vapN ) have demonstrated roles in macrophage infection, whereas the others are likely less or not at all relevant ( 16 , 17 ). A recent intriguing study ( 7 ) showed that, against expectation, host specificity associated with the different pVAP types (pVAPA and foals, etc.)…”
Section: Introductionmentioning
confidence: 99%